Preface: 6th International Symposium on Social Science and Management Innovation (SSMI 2024) - Zhou, Haiqing; Lambert, Richard (Transactions on Social Science, Education and Humanities Research, 2024)
6th International Symposium on Social Science and Management Innovation (SSMI 2024) was held in Macao, China during June 8-9, 2024. This conference was sponsored by Research Center of Engineering and Science, and was attended by academicians, researchers, entrepreneurs, government agencies and policy-makers, postgraduates from China and all over the world.The aim of the conference is to provide an interactive platform for the academicians, R & D organizations, industries, innovators, entrepreneurs, government agencies and policy-makers etc., from both China and abroad to exchange ideas on recent researches and advances in the domain of Social Science and Management Innovation with its prospective application in the various interdisciplinary domains of engineering. This two-day conference is being organized in technical association with Research Center of Engineering and Science and will include invited keynote talks and oral paper presentations from both academia and industry to ignite our young minds, to initiate them in the field of meaningful research and thereby enrich their existing knowledge.SSMI 2024 has received 97 manuscripts. And more than 20 submissions have been accepted by our reviewers and the Press. By submitting a paper to SSMI 2024, the authors agreed to the review process and understand that papers undergo a peer-review process. Manuscripts would be reviewed by appropriately qualified experts in the field selected by the Conference Committee, who would give detailed comments and-if the submission gets accepted-the authors submitted a revised version that considers this feedback. All papers were reviewed using a double-blind review process: authors declare their names and affiliations in the manuscript for the reviewers to see, but reviewers did not know each other's identities, nor did the authors receive information about who has reviewed their manuscript. The Committees invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit.With our warmest regards,SSMI 2024 Conference Committees